The impact of financial leverage towards financial performance: the international evidence from United States of America energy companies / Noor Zafirah Mohamad - Mohamad, Noor Zafirah (2017)
Financial performance is an important element in measuring the stability of a company. As to ensure that the company achieves the desired performance, it is important to determine the capital structure of a company correctly. This study aims to investigate how the financial leverage affects the financial performance of company by choosing 32 U.S energy companies as a study sample. As dependent variable, financial performance was indicated by return on asset meanwhile the financial leverage indicated by debt to asset ratio, debt to equity ratio and interest coverage ratio. The study period was from 2007 to 2016. Multiple linear regressions were used as to determine the relationship between independent variable and dependent variable. Based from the result, it shows that debt to equity ratio and interest coverage ratios of U.S energy companies do have significant positive relationship with their financial performance.